Accelerating perineal wound healing using binahong leaf extract sanitary pads - Asmaidar, Asmaidar; Runjati, Runjati; Santjaka, Aris; Cicilia, Fitri (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Background: Sanitary pads are essential for postpartum mothers to accommodate lochia and prevent infection in perineal wounds. Binahong leaves (Anredera cordifolia) contain flavonoids with antiseptic, antioxidant, and analgesic properties that promote wound healing by inhibiting microbial growth and reducing inflammation. However, research on the use of sanitary pads infused with Binahong leaf extract for perineal wound healing remains limited.Objective: This study investigates the effectiveness of Binahong leaf extract sanitary pads in accelerating postpartum perineal wound healing. Methods: A quasi-experimental study with a post-test-only randomized control group design was conducted at the Poasia Health Center, Kendari City. The study included postpartum mothers meeting specific inclusion and exclusion criteria, with a total sample of 34 participants (17 intervention, 17 control). The intervention group used Binahong leaf extract sanitary pads four times daily, while the control group relied on standard dry wound care. The intervention lasted seven days, and wound healing was assessed using the REEDA scale on days three, five, and seven.Results: The findings demonstrated a significant effect of Binahong leaf extract sanitary pads on perineal wound healing. The intervention group (2.52 ± 0.87) experienced faster wound recovery than the control group (5.23 ± 1.67) (p< 0.001).Conclusion: Binahong leaf extract sanitary pads effectively accelerate perineal wound healing in postpartum mothers and may serve as an alternative wound care approach.